Antiviral Activity of Pocapavir in a Randomized, Blinded, Placebo-Controlled Human Oral Poliovirus Vaccine Challenge Model. (7th December 2016) - Collett, Marc S.; Hincks, Jeffrey R.; Benschop, Kimberley; Duizer, Erwin; van der Avoort, Harrie; Rhoden, Eric; Liu, Hongmei; Oberste, M. Steven; McKinlay, Mark A.; Hartford, Marianne
Abstract: Background: Immunodeficient individuals who excrete vaccine-derived polioviruses threaten polio eradication. Antivirals address this threat. Methods: In a randomized, blinded, placebo-controlled study, adults were challenged with monovalent oral poliovirus type 1 vaccine (mOPV1) and subsequently treated with capsid inhibitor pocapavir or placebo. The time to virus negativity in stool was determined. Results: A total of 144 participants were enrolled; 98% became infected upon OPV challenge. Pocapavir-treated subjects (n = 93) cleared virus a median duration of 10 days after challenge, compared with 13 days for placebo recipients (n = 48; P = .0019). Fifty-two of 93 pocapavir-treated subjects (56%) cleared virus in 2–18 days with no evidence of drug resistance, while 41 of 93 (44%) treated subjects experienced infection with resistant virus while in the isolation facility, 3 (3%) of whom were infected at baseline, before treatment initiation. Resistant virus was also observed in 5 placebo recipients (10%). Excluding those with resistant virus, the median time to virus negativity was 5.5 days in pocapavir recipients, compared with 13 days in placebo recipients ( P < .0001). There were no serious adverse events and no withdrawals from the study. Conclusions: Treatment with pocapavir was safe and significantly accelerated virus clearance. Emergence of resistant virus and transmission of virus were seen in the context of a clinical isolation facility. Clinical Trials Registration: EudraCT 2011-004804-38.